Unravelling the kinetics of NH3 decomposition over highly active Ru/CeO2 catalysts: Effect of the support on H-poisoning and rate determining steps - Ivan Conti; Daniele Quattrin; Yi Qiu; Alessandro Trovarelli; Alessandra Beretta (Chemical Engineering Journal, 2026)

Mapping the advancements in floristic knowledge of Italy (2005–2025) - Gianniantonio Domina; Gianluigi Bacchetta; Fabrizio Bartolucci; Marco D’Antraccoli; Lorenzo Peruzzi; Adriano Stinca; Alessandro Alessandrini; Liliana Bernardo; Francesco Boscutti; Daniela Bouvet; Maurizio Bovio; Giacomo Calvia; et al. (Plant Biosystems, 2026)
Based on the evaluation of 3,902 local floristic references published between 2005 and 2025, an update to the floristic knowledge map of Italy is presented. To measure the progress in floristic knowledge across Italy’s administrative regions, the ‘Index of Floristic Knowledge Advancement’ (IFA) is proposed here. This index categorizes regions based on the proportion of potential improvement that has actually been achieved. Results showed an improvement in knowledge, most notably for Northern and Central Italy. Emilia-Romagna emerged as the most comprehensively documented region with the highest IFA value (0.81), followed by Lombardia (0.60), Friuli-Venezia Giulia (0.54), Trentino-Alto Adige and Veneto (0.53). In central Italy, Lazio (0.50), Sardegna (0.45) and Toscana (0.36) registered the highest scores. Over the past twenty years, 453 specific and subspecific taxa have been described from the Italian territory, the majority of which (443) are Italian endemics. Hieracium is the most represented genus (147 taxa). The marked progress documented is likely due to the accelerated impact of coordinated scientific projects, citizen science programs, the development of digital databases, and an increased focus on taxonomic research.

Liposomes self-assembly: numerically guided translation approach between microfluidic chip geometries - Marco Bellotti; Enrica Chiesa; Alessia Giglio; Ida Genta; Michele Conti; Ferdinando Auricchio; Alessandro Caimi (Chemical Engineering Journal, 2026)

Chestnut tannin induces gut degeneration in Aedes albopictus mosquito larvae - Linda Abenaim; Priscilla Farina; Angela Rosa Cuzzola; Loretta Guidi; Romano Dallai; David Mercati; Erika Carla Pierattini; Barbara Conti; Alessandro Mandoli (Environmental Science and Pollution Research, 2026)

Manufacturing 3D aortic root models for in vitro assessment of calcific aortic valve stenosis - Nicoletta Curcio; Luigi Bernardi; Antonio Rosato; Fabio Pappalardo; Martina Schembri; Michele Conti; Riccardo Vismara; Riccardo Gorla; Pietro Spagnolo; Lorenzo Menicanti; Alessandro Parolari; Giacomo Bortolussi; et al. (Annals of Biomedical Engineering, 2026)

The Effect Of Localized Circumferential Residual Stress On Pressurized Stress State Of CT Reconstructed Vessels: A Finite Element Study - Vittorio Lissoni; Martina Schembri; Giulia Luraghi; Alessandro Caimi; Virginia Fregona; Mauro Di Giancamillo; Jessica Bassi; Ferdinando Auricchio; Michele Conti; Gabriele Dubini; Francesco Migliavacca; Jose Felix Rodriguez Matas (Annals of Biomedical Engineering, 2026)
Purpose Residual stresses are intrinsic stresses present in arteries even in the absence of external loads or blood pressure. They originate during growth and remodeling and contribute to vascular mechanical equilibrium. Despite advances in computational methods, incorporating residual stresses into patient-specific vascular models remains challenging. Evidence regarding the influence of circumferential residual stresses on physiological loading in realistic anatomies is still limited. Methods We combined in vitro imaging, mechanical testing, and finite element (FE) simulations to incorporate residual stresses into a pressurized porcine aorta model. Medical images were acquired in both pressurized and zero-stress states, the latter obtained after 2 h of longitudinal cutting. Locally measured mechanical properties from distinct aortic regions were used to define an orthotropic hyperelastic material response. Residual stresses were restored by simulating vessel closure under displacement-controlled boundary conditions with a tied contact interface. Stress distributions were then compared in FE pressurization simulations performed with and without residual stresses. Results Residual stresses substantially influenced the predicted stress fields. They homogenized stress across the vessel thickness and reduced stress concentrations near the lumen. Moreover, lumen cross-sectional areas at 120 mmHg aligned more closely with experimental measurements when residual stresses were included. In contrast, neglecting residual stresses produced an average overestimation of lumen area by 4.84% and stress peaks up to 50% higher in the inner wall. Conclusion This study highlights the importance of accounting for residual stresses in biomechanical vascular simulations. Incorporating them improves prediction accuracy and reduces artificial stress concentrations, which is crucial for patient-specific risk assessment and surgical planning.

Transcript-protein discrepancy of glutamatergic receptor subunits in human iPSC-derived neurons: Implications for neurotoxicity testing - Melania Maria Serafini; Miriam Midali; Giacomo Grumelli; Alessandro Cutarelli; Marina Marinovich; Luciano Conti; Barbara Viviani (Toxicology Letters, 2026)

Exploring the plastivorous activity of Hermetia illucens (Diptera Stratiomyidae) larvae - Linda Abenaim; David Mercati; Alessandro Mandoli; Joachim Carpentier; Grégoire Noël; Barbara Conti; Rudy Caparros Megido; Romano Dallai (Environmental Science and Pollution Research, 2025)

The invasion history of Ambrosia psilostachya (Asteraceae) in Italy: first record and distribution over more than one century - Chiara Montagnani; Rodolfo Gentili; Gerhard Karrer; Sarah Caronni; Alicia Teresa Rosario Acosta; Michele Adorni; Alessandro Alessandrini; Nicola Maria Giuseppe Ardenghi; Gabriella Buffa; Fabrizio Bartolucci; Alessandra Belisario; Fabrizio Bonali; et al. (Plant Biosystems, 2025)

On the role of bacterial gut microbiota from supralittoral amphipod Talitrus saltator (Montagu, 1808) in bioplastic degradation - Alessandro Russo; Aldo D'Alessandro; Monica Di Paola; Benedetta Cerasuolo; Sonia Renzi; Niccolò Meriggi; Luca Conti; Jessica Costa; Rebecca Pogni; Tania Martellini; Alessandra Cincinelli; Alberto Ugolini; et al. (Science of The Total Environment, 2025)

Soft soap and linalool as potential management tools for Philaenus spumarius (Hemiptera: Aphrophoridae), vector of Xylella fastidiosa - Linda Abenaim; Priscilla Farina; Alessandro Mandoli; Giuseppe Conte; Barbara Conti (Crop Protection, 2025)

Computational-Aided Approach for the Optimization of Microfluidic-Based Nanoparticles Manufacturing Process - Marco Bellotti; Enrica Chiesa; Bice Conti; Ida Genta; Michele Conti; Ferdinando Auricchio; Alessandro Caimi (Annals of Biomedical Engineering, 2024)
In the last few years, the microfluidic production of nanoparticles (NPs) is becoming a promising alternative to conventional industrial approaches (e.g., nanoprecipitation, salting out, and emulsification-diffusion) thanks to the production efficiency, low variability, and high controllability of the production parameters. Nevertheless, the development of new formulations and the switching of the production process toward microfluidic platforms requires expensive and time-consuming number of experiments for the tuning of the formulation to obtain NPs with specific morphological and functional characteristics. In this work, we developed a computational fluid dynamic pipeline, validated through an ad hoc experimental strategy, to reproduce the mixing between the solvent and anti-solvent (i.e., acetonitrile and TRIS–HCl, respectively). Moreover, beyond the classical variables able to describe the mixing performances of the microfluidic chip, novel variables were described in order to assess the region of the NPs formation and the changing of the amplitude of the precipitation region according to different hydraulic conditions. The numerical approach proved to be able to capture a progressive reduction of the nanoprecipitation region due to an increment of the flow rate ratio; in parallel, through the experimental production, a progressive increment of the NPs size heterogeneity was observed with the same fluid dynamic conditions. Hence, the preliminary comparison between numerical and experimental evidence proved the effectiveness of the computational strategy to optimize the NPs manufacturing process. Graphical Abstract

Ingestion of chitosan-starch blends: Effect on the survival of supralittoral amphipods - Alberto Ugolini; Alessandro Russo; Jessica Costa; Alessandra Cincinelli; Tania Martellini; Luca Conti; Duccio Cavalieri; Luca Mercatelli; Rebecca Pogni (Science of The Total Environment, 2024)

Sex differences in Parkinson’s disease-related non motor symptoms: a focus on sleep problems - Roberta Bovenzi; Matteo Conti; Valentino De Franco; Mariangela Pierantozzi; Tommaso Schirinzi; Rocco Cerroni; Alessandro Stefani; Nicola Biagio Mercuri; Claudio Liguori (Acta Neurologica Belgica, 2024)
Parkinson’s disease (PD) symptomatology differs between females and males, yet the contribution of sex on sleep problems needs further analysis. Here, we aimed to investigate sex-specific patterns in the relationship between sleep problems, assessed using the Parkinson’s disease sleep scale (PDSS-2), non motor symptoms (NMS), measured by the NMS scale (NMSS), and health-related quality of life (HR-QoL), evaluated by the Parkinson’s disease questionnaire (PDQ-39), in a large cohort of PD patients. One-hundred-fifty-four PD patients were included in the study. Female PD patients (n = 62) exhibited a higher prevalence of sleep problems than males (n = 92), with nocturnal motor-related sleep issues being the most frequent. Sleep disturbances differently correlated with a range of NMS between the two sexes. In females, sleep problems mostly correlated with pain; on the other hand, sleep disturbances were linked to a frailer phenotype characterized by global dysautonomia, perception disturbances, and impaired cognitive function in males. Whether female PD patients experienced a lower HR-QoL than males, sleep disturbances were associated with a worse HR-QoL in both sexes. In conclusion, sleep problems in PD differently burden the two sexes, suggesting possible different etiopathogenesis, diagnostic investigations, and possibly tailored approaches.

Prioritizing conservation of terrestrial orchids: A gap analysis for Italy - Michele Lussu; Leonardo Ancillotto; Rocco Labadessa; Michele Di Musciano; Piero Zannini; Riccardo Testolin; Francesco Santi; David Dolci; Matteo Conti; Michela Marignani; Stefano Martellos; Lorenzo Peruzzi; et al. (Biological Conservation, 2024)

Bioplastics on marine sandy shores: Effects on the key species Talitrus saltator (Montagu, 1808) - Tania Martellini; Alessandro Russo; Alessandra Cincinelli; Saul Santini; Cristiana Lofrumento; Matteo Baini; Samuele Ciattini; Luca Conti; Francesca Mostardini; Luca Mercatelli; Alberto Ugolini (Science of The Total Environment, 2023)

HBIM for the preservation of a historic infrastructure: the Carlo III bridge of the Carolino Aqueduct - Alessandro Conti; Lidia Fiorini; Rosanna Massaro; Camilla Santoni; Grazia Tucci (Applied Geomatics, 2022)
The research on Carlo III bridge in Moiano (Benevento, Italy) has been an opportunity for testing the HBIM methodology to the architectural heritage in terms of not only gathering information but as a design tool. The bridge, almost without previous drawings and documents, was surveyed with an integrated approach using laser scanner, photogrammetry and topography. Data produced a metrically reliable HBIM model, complete with graphical and non-graphical information, to be used in a maintenance and restoration project.

Candida gut colonization, yeast species distribution, and biofilm production in Clostridioides difficile infected patients: a comparison between three populations in two different time periods - Grazia Brunetti; Alessandro Giuliani; Anna Sara Navazio; Camilla Paradisi; Flavia Raponi; Libenzio Adrian Conti; Giammarco Raponi (Brazilian Journal of Microbiology, 2021)
Candida gut colonization and yeast biofilm production capacity were investigated, by means of XTT reduction assay, in Clostridioides difficile infected (CDI) patients, in non-CDI diarrheic patients, and in healthy donors in two different time periods (2013–2015 and 2018–2019 respectively). Candida gut colonization was significantly ( p < 0.001) associated to C. difficile infection, and to patients infected with hypervirulent C. difficile strains bearing the tcdC deletion at nucleotide 117 ( p = 0.0003). Although there was not a prevalent yeast species in CDI patients, C. albicans was the species significantly ( p < 0.001) associated to both the infections sustained by the non-hypervirulent C . difficile strains and those caused by the hypervirulent strain ( p = 0.001). The biofilm production by the yeasts isolated from the CDI patients and from non-CDI diarrheic patients did not differ significantly. However, a significantly ( p = 0.007) higher biofilm production was observed in the Candida strains, particularly C. albicans , isolated from healthy donors compared to that of the yeasts cultured from CDI patients. Seasonal occurrence was observed in the isolation rate of CDI and non-CDI diarrheic cases ( p = 0.0019), peaking in winter for CDI patients and in spring for non-CDI diarrheic patients. Furthermore, seasonality emerged in the gut colonization by Candida of CDI patients in the winter. It seems, therefore, that the reduced capacity of biofilm production by Candida strains isolated from CDI patients might have a role in the development of C. difficile infection, probably facilitating the spread of the bacteria into the gut thus amplifying their pathogenic action.

IDPlanT: the Italian database of plant translocation - Thomas Abeli; Martina D’Agostino; Simone Orsenigo; Fabrizio Bartolucci; Rita Accogli; Giulia Albani Rocchetti; Claudia Alessandrelli; Arianna Amadori; Filippo Amato; Claudia Angiolini; Silvia Assini; Gianluigi Bacchetta; et al. (Plant Biosystems, 2021)

Red list of threatened vascular plants in Italy - Simone Orsenigo; Giuseppe Fenu; Domenico Gargano; Chiara Montagnani; Thomas Abeli; Alessandro Alessandrini; Gianluigi Bacchetta; Fabrizio Bartolucci; Angelino Carta; Miris Castello; Donatella Cogoni; Fabio Conti; et al. (Plant Biosystems, 2021)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Community assembly processes along a sub-Mediterranean elevation gradient: analyzing the interdependence of trait community weighted mean and functional diversity - Alessandro Bricca; Luisa Conti; Maria Federico Tardella; Andrea Catorci; Marco Iocchi; Jean-Paul Theurillat; Maurizio Cutini (Plant Ecology, 2019)

Plant–environment interactions through a functional traits perspective: a review of Italian studies - Stefano Chelli; Michela Marignani; Elena Barni; Alessandro Petraglia; Giacomo Puglielli; Camilla Wellstein; Alicia T. R. Acosta; Rossano Bolpagni; Luca Bragazza; Giandiego Campetella; Alessandro Chiarucci; Luisa Conti; et al. (Plant Biosystems, 2019)

Whale Shark Tourism: Impacts on Coral Reefs in the Philippines - C. W. Martin Wong; Inga Conti-Jerpe; Laurie J. Raymundo; Caroline Dingle; Gonzalo Araujo; Alessandro Ponzo; David M. Baker (Environmental Management, 2019)

Mast cells participate in allograft rejection: can IL-37 play an inhibitory role? - Pio Conti; Alessandro Caraffa; Gianpaolo Ronconi; Spiros K. Kritas; Filiberto Mastrangelo; Lucia Tettamanti; Ilias Frydas; Theoharis C. Theoharides (Inflammation Research, 2018)

Impact of mast cells in depression disorder: inhibitory effect of IL-37 (new frontiers) - Pio Conti; Alessandro Caraffa; Gianpaolo Ronconi; Chiara M. Conti; Spiros K. Kritas; Filiberto Mastrangelo; Lucia Tettamanti; Theoharis C. Theoharides (Immunologic Research, 2018)

Potential therapeutic use of IL-37: a key suppressor of innate immunity and allergic immune responses mediated by mast cells - Pio Conti; Francesco Carinci; Gianfranco Lessiani; Enrico Spinas; Spyridon K. Kritas; Gianpaolo Ronconi; Alessandro Caraffa; Theoharis C. Theoharides (Immunologic Research, 2017)

The Ventotene Volcanic Ridge: a newly explored complex in the central Tyrrhenian Sea (Italy) - Marco Cuffaro; Eleonora Martorelli; Alessandro Bosman; Alessia Conti; Sabina Bigi; Filippo Muccini; Luca Cocchi; Marco Ligi; Giovanni Bortoluzzi; Davide Scrocca; Simonepietro Canese; Francesco L. Chiocci; et al. (Bulletin of Volcanology, 2016)

Lateral specialization in unilateral spatial neglect: a cognitive robotics model - Daniela Conti; Santo Di Nuovo; Angelo Cangelosi; Alessandro Di Nuovo (Cognitive Processing, 2016)

Heterogeneous drug target expression as possible basis for different clinical and radiological response to the treatment of primary and metastatic renal cell carcinoma: suggestions from bench to bedside - Matteo Santoni; Daniele Santini; Francesco Massari; Alessandro Conti; Roberto Iacovelli; Luciano Burattini; Giampaolo Tortora; Massimo Falconi; Rodolfo Montironi; Stefano Cascinu (Cancer and Metastasis Reviews, 2014)

Operant, oral alcoholic beer self-administration by C57BL/6J mice: effect of BHF177, a positive allosteric modulator of GABAB receptors - Alessandro Orrù; Daniele Fujani; Chiara Cassina; Mirko Conti; Angelo Di Clemente; Luigi Cervo (Psychopharmacology, 2012)

Atmospheric background trace elements deposition in Tierra del Fuego region (Patagonia, Argentina), using transplanted Usnea barbata lichens - Marcelo Enrique Conti; Maria Grazia Finoia; Beatrice Bocca; Giustino Mele; Alessandro Alimonti; Anna Pino (Environmental Monitoring and Assessment, 2012)

Hyptis suaveolens and Hyptis spicigera (Lamiaceae) essential oils: qualitative analysis, contact toxicity and repellent activity against Sitophilus granarius (L.) (Coleoptera: Dryophthoridae) - Barbara Conti; Angelo Canale; Pier Luigi Cioni; Guido Flamini; Alessandro Rifici (Journal of Pest Science, 2011)

Baseline Trace Metals in Seagrass, Algae, and Mollusks in a Southern Tyrrhenian Ecosystem (Linosa Island, Sicily) - Marcelo Enrique Conti; Beatrice Bocca; Marta Iacobucci; Maria Grazia Finoia; Mauro Mecozzi; Anna Pino; Alessandro Alimonti (Archives of Environmental Contamination and Toxicology, 2010)

Influence of weight on the content of trace metals in tissues of Mytilus galloprovincialis (Lamarck, 1819): a forecast model - Marcelo Enrique Conti; Marta Iacobucci; Gaetano Cecchetti; Alessandro Alimonti (Environmental Monitoring and Assessment, 2008)

Cytomorphological study on human submandibular gland following treatment with secretagogue drugs - Francesca Testa Riva; Roberto Puxeddu; Francesco Loy; Gabriele Conti; Alessandro Riva (Cell and Tissue Research, 2006)